Pituitary aspergillosis in a kidney transplant recipient and review of the literature. Issue 5 (3rd October 2013) - Vijayvargiya, P.; Javed, I.; Moreno, J.; Mynt, M.A.; Kotapka, M.; Zaki, R.; Ortiz, J.
Abstract Pituitary aspergillosis is a very rare disease, documented in only 12 cases. Although seen in both immunocompetent and immunocompromised patients, serious invasive sequelae, such as meningoencephalitis and death, have been noted in immunocompromised patients. Immunocompromised patients are susceptible and require complex multidisciplinary care to contain the spread of infection and maximize outcomes. This is the first case report, to our knowledge, of pituitary aspergillosis in the setting of an organ transplant. A 68‐year‐old woman presented with cephalgia, left temporal hemianopsia, and ptosis. Non‐contrast magnetic resonance imaging of the head revealed a sellar mass, which was believed to be a benign pituitary adenoma. She underwent trans‐sphenoidal resection, and subsequent histopathologic examination showed aspergillosis. She was subsequently started on voriconazole. On postoperative day 3, she developed a left anterior cerebral artery ischemic stroke, likely from Aspergillus angioinvasion and occlusion. Her mental status declined further and she died when care was withdrawn.